2021
DOI: 10.3390/su13116081
|View full text |Cite
|
Sign up to set email alerts
|

Towards Sustainable Livestock Production: Estimation of Methane Emissions and Dietary Interventions for Mitigation

Abstract: The increasing need for sustainable livestock production demands more research in the field of greenhouse gas (GHG), particularly methane (CH4), measurement and mitigation. Dietary interventions, management, and biotechnological strategies to reduce the environmental impacts and economic implications of enteric CH4 emissions are needed. While the use of biotechnological interventions and management strategies can be challenging on a routine basis, feed additive supplementation appears to be the most researched… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 170 publications
(174 reference statements)
0
11
0
Order By: Relevance
“…Another possible reason for the decrease in CH 4 from the WD and BD-fed animals could be attributed to the higher propionate concentration in the WD-and BD-fed animals compared with the MD-fed animals and the decreased concentration of butyrate in the BD-fed animals than the WD and MD-fed sheep. The increased propionate production and decreased butyrate production in the rumen of BD-fed sheep could have freely available hydrogen in the rumen that would otherwise be used by methanogens to reduce CO 2 to produce CH 4 [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another possible reason for the decrease in CH 4 from the WD and BD-fed animals could be attributed to the higher propionate concentration in the WD-and BD-fed animals compared with the MD-fed animals and the decreased concentration of butyrate in the BD-fed animals than the WD and MD-fed sheep. The increased propionate production and decreased butyrate production in the rumen of BD-fed sheep could have freely available hydrogen in the rumen that would otherwise be used by methanogens to reduce CO 2 to produce CH 4 [15].…”
Section: Discussionmentioning
confidence: 99%
“…Ruminants' contribution to global warming is one of the most contentious topics of the 21st century and the emissions are mainly in the form of enteric methane (CH 4 ) [15]. The CH 4 alone accounts for 47% of the livestock sector's total GHG emissions and 17.3% of global GHG emissions [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Mitigation strategies that do not hinder production while effectively reducing CH 4 emissions in cattle are necessary. In practice, sustainable cattle production should be economically viable, ensuring high efficiency and low emissions per unit of production [20]. Previous studies have demonstrated that increased livestock production contributes to higher CH 4 emissions unless effective strategies to mitigate GHG emissions in livestock systems are implemented [21].…”
Section: Introductionmentioning
confidence: 99%
“…, caproate, ethanol and propanol. These dynamics are imminently important for ruminant animals as they address the issue of acidosis(Prathap et al, 2021;Souza et al, 2020) …”
mentioning
confidence: 99%